Hubungan Proyek Penguatan Profil Pelajar Pancasila (P5) dengan Tingkat Kepuasan Orang Tua di PAUD Permata Bunda SKB Mojoagung Jombang - Artikasari, Dian; Artha, I Ketut Atmaja Johny (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
This research is motivated by the decline in the character of a nation caused by the rapid flow of globalization and technological development which brings many conveniences, of course it is also not free from several negative impacts, even on all elements of society, one of which is children who are also exposed. This is the background to this research, namely the existence of a new project in the Merdeka Curriculum after the Covid-19 pandemic with the hope that children will further develop their potential in a positive direction and interact with their surroundings. This research uses a quantitative research approach with a correlational research type. Taking respondents at PAUD Permata Bunda with a target of 30 parents. Data collection techniques use online questionnaires and documentation. Meanwhile, the data analysis technique uses the Product Moment formula to analyze the questionnaire. The research results show that Play Group (KB) services have a significant positive relationship with parental satisfaction at PAUD Permata Bunda as indicated by the correlation value between the two research variables of 0.782. If the number of respondents or the value of N=30 with a significance level of 5% then the r-table value is 0.349. Thus the r-count of 0.782 is greater than the r-table of 0.349. So, if the implementation of the Project for Strengthening the Profile of Pancasila Students (P5) is better, the level of parental satisfaction will increase and vice versa, if the Project for Strengthening the Profile of Pancasila Students (P5) is bad, the level of parental satisfaction will be lower.